Minori Stranieri Non Accompagnati: rappresentazioni dell’infanzia nei centri di accoglienza in Italia, Svezia, Cipro e Spagna. Per un approccio pedagogico inclusivo allo sviluppo della competenza professionale degli operatori. - LAMPUGNANI, PAOLA ALESSIA (Università degli studi di Genova, 2019)
The refugee crisis we are witnessing in the lasts years represents one of the thorniest themes in all the European Governments agenda. In the lasts three years the number of persons escaping from their countries is constantly and dramatically increased, and over 35% of them are Children. The asylum seekers crisis - particularly the unaccompanied Children asylum seekers - requests to every country - those they leave, those they cross and those in which they seek asylum - a duty to protect and safeguard the rights guaranteed under the Convention on the Rights of the Child (1979). According UNICEF’s seven points plan for refugee and migrant Children (UNICEF, 2016): - Unaccompanied or separated Children must be kept safe - The best interests of the Child should be a primary consideration in any decision concerning that Child - Children must be given access to services such as health and education. In order to pursue these objects, Local social services thus need to overcome a merely welfarism action-model, in order to promote educational design and research grounded on social workers professional skills. The research aimed at investigating the construction of social representations of Childhood in contexts involving asylum seekers or refugee families/unaccompanied children. The research has been conducted in the context of intercultural studies, which developed different explanation models of intercultural relationships. It specifically referred to studies on intercultural sensitivity (Bennett, 1998) and on intercultural competence (Spitzberg, 2009; Berardo & Deardorff, 2012; Jackson, 2012; Odag, Wallin & Kedzior, 2015). The conceptual framework refers to: right-based and care-based education [King, 2004; Premoli, 2012; Grange, 2014] and intercultural education (Cambi, 2001; Benhabib, 2002; Santerini, 2003; Mantovani, 2004; Abdallah Pretceille, 2013; Pinto Minerva, 2015). In the frame of the interpretivist paradigm and of a qualitative approach, a participatory action-research (Rapoport, 1970; Whyte, 1991; ...